A review of construction waste management and initiatives in Malaysia / Noor Rizallinda Ishak and Siti Akhtar Mahayuddin - Ishak, Noor Rizallinda; Mahayuddin, Siti Akhtar (2021)
Construction industry is considered as one of the major stimulant industries that not only generates wealth, but also the social and economic growth of the country. However, this industry also produces large amounts of waste from the construction activities. This paper is set out to analyse the existing literature on construction waste management in Malaysia and the initiatives that have been implemented in the Malaysian construction industry. Systematic reviews have been carried out on the initiatives that have been implemented on construction waste management in Malaysia. This study is guided by the PRISMA Statement (Preferred Reporting Items for Systematic reviews and Meta-Analyses) review method, a systematic review of the Scopus and Web of Science databases of which has identified 17 related studies. Further review of these articles resulted in four main themes namely technology, strategies, enforcement and also procurement. These four themes further produced a total of 14 sub-themes. A total of 35 studies focused on the strategies initiative which reported the highest number of study areas, followed by enforcement initiative with 16 studies. Next is technology initiative reported 11 studies and the least was procurement initiative with 10 studies. Thus, these initiatives show their positive impact to the environment and the construction waste management practice in Malaysia